Effects of dietary fiber on postprandial glucose in healthy adults - Yesmin, F; Ali, MOI; Sardar, MMR; Munna, MK; Baksh, S (Mediscope, 2018)
Frequently and persistently raised glucose level causes numerous complications. So it is important to find out a component of diet that can improve glucose homeostasis after ingestion of food without causing any side effect or complication. The aim of this randomized controlled clinical trial study was to verify the effect of dietary fiber on postprandial blood sugar (PPBS). The study was carried out in a sample of fifty healthy adult subjects at the Department Physiology of Rajshahi Medical College during the period from January 2014 to December 2014. Fasting blood sugar of the subjects was estimated before ingestion of identical glucose drink with or without dietary fiber (ispaghula husk) and PPBS was measured at 30, 60 and 120 min after the drink. The mean plasma glucose concentrations after a 50 gm oral glucose load significantly (p < 0.05, p < 0.001) decreased at 30, 60 and 120 min in both condition with dietary fiber and without dietary fiber. The mean plasma postprandial glucose concentration in condition with dietary fiber was significantly (p < 0.001) lower than the corresponding value without dietary fiber. The study suggests that ingestion of water soluble dietary fiber along with glucose drink reduces sharp rise as well as sustained rise of postprandial glucose. Mediscope Vol. 6, No. 1: Jan 2019, Page 25-29